CHEMOTHERAPY-INDUCED NEUTROPENIA IN HIV POSITIVE PATIENTS WITH LYMPHOMA: COMPARISON OF PEGFILGRASTIM WITH DAILY FILGRASTIM ADMINISTRATION. - Luciana Teofili; Immacolata Izzi; Eugenia Rosa Nuzzolo; Giancarlo Scoppettuolo; Katleen de Gaetano Donati; Lorenza Torti; Marianna Rossi (Mediterranean Journal of Hematology and Infectious Diseases)
We retrospectively compared the incidence of neutropenia  in two groups of  HIV patients with lymphoma,  who underwent chemotherapy supported by once-per-cycle administration of pegfilgrastim or by daily subcutaneous injection of filgrastim, respectively. Our findings indicate that pegfilgrastim and filgastrim produce similar results in preventing both neutropenia and febrile neutropenia.